2009
DOI: 10.1093/brain/awp099
|View full text |Cite
|
Sign up to set email alerts
|

Reduced O-GlcNAcylation links lower brain glucose metabolism and tau pathology in Alzheimer's disease

Abstract: It has been established for a long time that brain glucose metabolism is impaired in Alzheimer's disease. Recent studies have demonstrated that impaired brain glucose metabolism precedes the appearance of clinical symptoms, implying its active role in the development of Alzheimer's disease. However, the molecular mechanism by which this impairment contributes to the disease is not known. In this study, we demonstrated that protein O-GlcNAcylation, a common post-translational modification of nucleocytoplasmic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
312
3
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 369 publications
(329 citation statements)
references
References 57 publications
11
312
3
3
Order By: Relevance
“…Glutamine:fructose‐6‐phosphate amidotransferase (GFAT) is the rate‐limiting enzyme of this pathway. We injected a specific inhibitor of GFAT, 6‐diazo‐5‐oxonorleucine (DON), intracerebroventricularly to downregulate O‐GlcNAcyaltion of proteins in rat brains (Liu et al ., 2009). We found that DON significantly suppressed protein O‐GlcNAcylation in rat brains (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Glutamine:fructose‐6‐phosphate amidotransferase (GFAT) is the rate‐limiting enzyme of this pathway. We injected a specific inhibitor of GFAT, 6‐diazo‐5‐oxonorleucine (DON), intracerebroventricularly to downregulate O‐GlcNAcyaltion of proteins in rat brains (Liu et al ., 2009). We found that DON significantly suppressed protein O‐GlcNAcylation in rat brains (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The phosphorylation of tau at the PKA site―Ser214―was decreased, but at a non‐PKA site―Thr205― was increased (Fig. 5B), the latter of which is due to a different mechanism (Liu et al ., 2009). These results are consistent with the positive regulation of PKA activity by O‐GlcNAcylation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations